Geomorphological Changes and Permafrost Dynamics: Key Factors in Changing Arctic Ecosystems. An Example from Bylot Island, Nunavut, Canada - Allard, Michel (Geoscience Canada)

(untitled) (The Geological Association of Canada, 1996)
Summary Geomorphological changes related to erosion and sedimentation, periglacial processes, and the thermal regime of permafrost can provide important information on the impact of climatic changes on the terrain in arctic regions. In some areas, organic- (peat-) rich stratigraphie sequences can lead to the interpretation of past changes related to the variable intensity of geomorphological processes.In the Arctic, the dual accumulation of peat and sand is closely related to syn-geneic aggradation of permafrost andto frost cracking, leading to the forma-tion of tundra polygons. Eolian activity may increase in colder and drier periods. Observations of surface changes (geomorphology and vegetation) in a regional network of sensitive sites, along with climate and permafrost temperature monitoring, constitute a comprehensive method to assess the impact of climatic changes on land systems in the Arctic. One such site, on Bylot Island, provides a good example.